Challenges and difficulties of realizing digital resources for their role in light of the Corona pandemic as a model - Al-Anazi, Thamer Attih Sber (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the challenges and difficulties that prevent digital resources from achieving their role in the light of the Corona pandemic in the fields of education, health, tourism, business and industry, The study also used the qualitative method, The study reached several results, the most important of which is the lack of a digital infrastructure that contributes to the realization of digital resources for their role, in addition to the lack of a clear vision of digital operations and support / leadership from senior management, and the lack of cooperation of business companies to cooperate on technical solutions, and the study recommended the need to provide A digital infrastructure that contributes to the realization of digital resources for their role, and also recommended the need to spread digital culture among citizens